EiA Regional Climate Prioritization Exercise: PAiCE Supporting Data - Steward, Peter Richard; Rosenstock, Todd Stuart; Wood-sichra, Ulrike (2024)
Crop production, harvested area and value of production data from MapSPAM to inform the PAiCE tool economic valuations in the Excellence in Agronomy (EiA) regional platforms. Values are provided for four platforms in West and Central Africa, one in Southern Africa and one in North Africa. This work is supported by the CGIAR Excellence in Agronomy Initiative Climate add-on. Metodology:Crop production and value of production data from MapSPAM were extracted using the AICCRA CP tool for EiA regional platforms. For more details see the readme document provided.